Three new species of nocturnal geckos of the Paroedura oviceps clade from xeric environments of Madagascar (Squamata: Gekkonidae) - Glaw, Frank; Köhler, Jörn; Vences, Miguel (Zootaxa, 2018)
We describe three new gecko species of the Paroedura oviceps clade, diagnosed by deep divergences in mitochondrial DNA, absence of haplotype sharing in two nuclear genes (sacs and kiaa1239), and morphological differences. Paroedura spelaea sp. nov. is an extremely slender species from karst habitats in the limestone massif of the Tsingy de Bemaraha National Park in western Madagascar, morphologically reminiscent of P. homalorhina but distinguished by the absence of distinct dorsal rows of spiny tubercles. Paroedura fasciata sp. nov. from the small karstic island Nosy Hara in northern Madagascar is phylogenetically placed sister to P. spelaea despite radical morphological differences. It is morphologically most similar to P. hordiesi from the geographically close Montagne des Français massif, but is smaller, has slightly more spiny dorsal scales, and a distinctive colour pattern with light grey dorsal crossbands. The third species, Paroedura kloki sp. nov., is known from Ankarafantsika National Park and the western slopes of Makira, two sites of dry to transitional forest in western Madagascar. It is at least partly arboreal and morphologically very similar to P. oviceps, from which it differs by spiny scales extending over its entire tail. Although incomplete, the available phylogenetic evidence suggests that the karst specialists in the P. oviceps clade (P. fasciata, P. homalorhina, P. hordiesi, P. spelaea) form a monophyletic group which might have diversified by vicariance after becoming isolated, respectively, in their limestone habitats in Tsingy de Bemaraha, Ankarana, Nosy Hara and Montagne des Français.